2020
DOI: 10.1177/0886260520965974
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Abuse Classes for Incarcerated Men and Women: Are There Unique Gender Patterns in Abuse Classes?

Abstract: Childhood adversity is predictive of poorer health and behavioral health outcomes in adulthood. Males and females are known to experience different types of childhood adversity, with females experiencing more sexual and emotional harm in childhood. Latent class analysis (LCA) has been used to identify patterns among types of childhood adversity. These studies have constructed class structures using single gender or blended gender samples. Class structures based on blended gender samples, however, may misrepres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Our study focused exclusively on incarcerated males. Previous research has found that male and female incarcerated people differ in several aspects (e.g., mental health, substance‐dependence disorders, violence; Binswanger et al, 2010; Wolff et al, 2020), therefore research should replicate these findings with samples of incarcerated women to explore whether perceptions and usage of the complaint system differ by gender. This is particularly relevant as previous research in other jurisdictions suggests that incarcerated women and youth may be less likely to seek a review by the Ombudsman or know about the system to do so (Prison and Probations Ombudsman for England and Wales, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Our study focused exclusively on incarcerated males. Previous research has found that male and female incarcerated people differ in several aspects (e.g., mental health, substance‐dependence disorders, violence; Binswanger et al, 2010; Wolff et al, 2020), therefore research should replicate these findings with samples of incarcerated women to explore whether perceptions and usage of the complaint system differ by gender. This is particularly relevant as previous research in other jurisdictions suggests that incarcerated women and youth may be less likely to seek a review by the Ombudsman or know about the system to do so (Prison and Probations Ombudsman for England and Wales, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The current study uses a person-centered approach, based on the interrelations among child harm, to address methodological limitations of previous research. While research suggests that men and women have unique patterns of childhood harm (Wolff et al, 2020), very few studies have been conducted with incarcerated women specifically. This is an important limitation because such analyses could inform program planning and development that address the unique treatment needs of incarcerated women.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Stress ranks among the wide variety of causes and well-known risk factors leading to drug addiction and relapse, with addictive disorders being chronic and recurrent [ 12 ]. Childhood trauma is a risk factor for anxiety, mental disorders development, and substance use [ 13 ], which are more common in women [ 14 , 15 ]; therefore, drug addiction is more pronounced in them than in men [ 16 ]. The data show an increased use of illicit drugs such as opioids among women.…”
Section: Introductionmentioning
confidence: 99%